1999
DOI: 10.1002/1529-0131(199902)42:2<373::aid-anr21>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of the inflammatory state in active juvenile rheumatoid arthritis with hypo-high-density lipoproteinemia and reduced lipoprotein-associated platelet-activating factor acetylhydrolase activity

Abstract: Objective. To investigate the relationship between the quantitative and qualitative abnormalities of apolipoprotein B (Apo B)-and Apo A-I-containing lipoproteins and between lipoprotein-associated plateletactivating factor acetylhydrolase (PAF-AH) activity in patients with juvenile rheumatoid arthritis (JRA) as a function of the inflammatory state.Methods. Twenty-six JRA patients and 22 ageand sex-matched control subjects with normal lipid levels participated in the study. Fourteen patients had active disease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1
6

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 48 publications
(47 reference statements)
4
18
1
6
Order By: Relevance
“…This decrease was associated with the presence of anti-apo A-I antibodies in 32% of patients. 49 Recently, it was shown that the inflammatory condition in juvenile rheumatoid arthritis was associated with hypo-high density lipoproteinemia 50 and a significant decrease in apo A-I concentration in patient plasma. In rheumatoid arthritis, the levels of circulating apo A-I and HDL cholesterol in untreated patients are lower than in normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease was associated with the presence of anti-apo A-I antibodies in 32% of patients. 49 Recently, it was shown that the inflammatory condition in juvenile rheumatoid arthritis was associated with hypo-high density lipoproteinemia 50 and a significant decrease in apo A-I concentration in patient plasma. In rheumatoid arthritis, the levels of circulating apo A-I and HDL cholesterol in untreated patients are lower than in normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Informed consent was obtained from the older children (aged ≥18 years) and from the parents of all children. Disease activity was evaluated with a method previously described [24]. Mouth opening capacity was assessed with a ruler by asking the patient to open the mouth as wide as possible and measuring between the central incisors, adding the vertical overbite [25].…”
Section: Methodsmentioning
confidence: 99%
“…6 This enzyme activity has been reported to correlate with several inflammatory diseases such as asthma, 7,8 systemic lupus erythematosus 9 and juvenile rheumatoid arthritis. 10 Furthermore, previous reports have revealed that the polymorphism of pPAF-AH gene (PLA2G7) influences its activity. Miwa et al 11 discovered an autosomal recessive heredity form of pPAF-AH deficiency in Japanese families.…”
Section: Introductionmentioning
confidence: 99%